Analisis Perkembangan Akad-Akad Di Bank Syariah - Riyan Pradesyah (Faculty of Islamic Religion, Universitas Muhammadiyah Sumatera Utara, 2019)
Islamic banking has a role in developing the economy in Indonesia, in this case of course Islamic financial institutions provide financing to the community, to develop the economy. This study aims to describe the use of mudharabah and murabahah contracts used by Islamic financial institutions, in terms of providing funding to the public. When viewed from the development of Islamic financial institutions, from year to year they continue to experience a significant increase, only the people are still reluctant to conduct transactions in Islamic financial institutions. So this of course will impact on the contracts used in the transaction. For this reason, the focus of this research is only on the development of mudharabah and murabahah contracts in Islamic financial institutions.Keywords: Islamic financial institutions, contracts in Islamic financial institutions